Contact pressure evaluation of a gear pair along the line of action using finite element analysis - Patil, S. (2013)
In loaded gears, contact behavior along the line of action changes tremendously. This leads to variation in gear contact conditions along the tooth flank, which may cause the failures such as surface wear, scuffing and pitting at different positions on the tooth surface. Hence, the information on the instant contact behavior along the line of action is crucial. However its evaluation for real gear conditions is very complicated. In this paper, the contact pressure for a pair of mating spur gears has been determined by Finite Element Analysis (FEA) using ANSYS software. The contact pressure results are then verified by twin-disc experimental results and the Hertzian contact pressure equation. The ANSYS results show the similar trend with the twin-disc test results, indicating that the FEA modelling is successful and provides good results. Â© (2013) Trans Tech Publications, Switzerland.